“El olvido está lleno de memoria” : estudo de caso do sítio de consciência Villa Grimaldi como meio de comunicação : a didática dos direitos humanos e a cultura da memória - Hernandez Briones, Marcia Cristina (2015)
The present thesis aims to develop a reception theory of the site of conscience Corporación Parque por la paz Villa Grimaldi. This place of memory is approached here as a mean of communication, since it intends not only to inform but also educate new generations about crimes against humanity that occurred due to Chile’s military coup. The main research problem is understanding how this site of conscience is used today as a mean of communication and how it works in favor of human rights education. The object is built on the interface of many subjects, but specially the treatment of memory and didactics of human rights. Its purpose is to analyze the reception of 30 visitors to Villa Grimaldi, through semistructured interviews. Charts and comparative tables resulting from the display formatting of materials and answers given by the visitors allow the offering of a typology of contents categories, based on the methodology of Discursive Textual Analysis (MORAES, 2011). The paper describes the memorial pedagogy and human and technological resources used (for it sees them as support for the present case study), as well as the memorial format – as a place able to spread messages that could be decoded by receptors/visitors. Theories emphasizing the idea of sites of conscience as means of communication will be considered. Among them, situationism (symbolic interactionism) and the Medium Theory, as stated by Joshua Meyrowitz. Authors such as Andreas Huyssen (2007, 2000, 1997), Marshall McLuhan (1964), Tunbridge & Ashworth (1996), Maurice Halbwachs (1950) and Pierre Nora (2011) will be approached, among others. The joining of both referencials contemplate topics brought up by spaces of memory and it allows a case study with the purpose of recognizing a site of conscience as a mean of communication.